MENINGKATKAN HASIL BELAJAR SISWA DENGAN MENGGUNAKAN MODEL INQUIRY PADA MATERI TUMBUHAN DIKELAS IV UPT SPF SDN 105338 DENAI KUALA T.A 2020/2021 - Fahmi Roji; Rizka Hidayah Husin Lubis (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2020)
This research examines the improvement of science learning outcomes using the Inquiry Model in Class IV UPT SPF SDN 105338 Denai Kuala. The theory used is PTK (Classroom Action Research) is an activity carried out by educators or together with other people in a collaborative manner which aims to improve or improve the quality or learning process in the classroom. In its implementation, the researcher acts as a teacher who will conduct teaching by applying a learning model that has been planned and compiled, while the class teacher acts as an observer during learning. The method used is the Inquiry Learning Model. Inquiry Learning Model is a learning model specifically designed to develop student activities in the learning process as a support for declarative knowledge and procedural knowledge of learning materials. The results of the study and discussion showed that there were 30 students or none of them who got a complete score with an average score of 19.33. Furthermore, after being given action using the Inquiry learning model in cycle I, student learning outcomes increased from the previous by an average of 38.67 where as many as 6 students (20%) got complete scores and 24 students (80%) got incomplete scores. Then in the second cycle test results obtained an average of 80.67 with 28 students (93.33%) getting complete scores and 2 students (6.67%) getting incomplete scores. Thus, the results of this study indicate that there is an increase in learning outcomes from before to after the application of the Inquiry learning model, more clearly on the development of student learning outcomes in science subjects, the subject matter "Plants".